BEARDLESS BARB Cyclocheilichthys apogon (VALENCIENNES, 1842) (CYPRINIFORMES: CYPRINIDAE) IN MADURA ISLAND, INDONESIA - Veryl Hasan; Soemarno Soemarno; Maheno Sri Widodo; Dewa Gede Raka Wiadnya (BIOTROPIA, 2021)
The freshwater fish Beardless Barb Cyclocheilichthys apogon (Valenciennes, 1842) is a native species of Southeast Asia, including the western Indonesia area (Borneo, Sumatra, and Java). Previously, the species was found only in the mainland of Java Island. This paper provides the first record of C. apogon in the Lembung River, one of the major rivers in Madura Island, Indonesia, thereby extending the species distribution up to 150 km northeast from the place of earlier record. The specimens of C. apogon were characterized as follows: dorsal fin rays 12; anal fin rays 8–9; pectoral fin rays 17–18; lateral line scales 34–35. A detailed description of the morphological characters of the specimen is provided in this manuscript.